2020
DOI: 10.1088/1361-6463/abc7d8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma dynamics at the preionization stage in discharge-based EUV lasers

Abstract: In this paper we present the results of a detailed numerical investigation of plasma formed at the preionization stage of extreme ultraviolet (EUV) lasers based on nanosecond capillary discharges. Despite the general consensus that preliminary ionization is one of the features that have originally allowed creating stable and efficient lasers operated in argon-filled capillaries, little attention has been paid to the observed sensitivity of their performance to the properties of the preionizing current pulse. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The concave shape is due to plasma pressure being almost constant along the capillary radius, while plasma itself is hotter on the axis and cooler at the periphery as a result of contact with the capillary wall. This also explains the greater overall degree of inhomogeneity of a profile for higher prepulse current amplitudes (for a detailed discussion of plasma properties at this stage and their dependence on prepulse parameters see [19]). In figure 4 presented are the calculated temporal dependencies of electron density (figure 4(a)) and electron temperature (figure 4(b)) at the capillary axis for cases of different prepulse current amplitudes together with the case of uniform initial density distribution.…”
Section: Simulation Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The concave shape is due to plasma pressure being almost constant along the capillary radius, while plasma itself is hotter on the axis and cooler at the periphery as a result of contact with the capillary wall. This also explains the greater overall degree of inhomogeneity of a profile for higher prepulse current amplitudes (for a detailed discussion of plasma properties at this stage and their dependence on prepulse parameters see [19]). In figure 4 presented are the calculated temporal dependencies of electron density (figure 4(a)) and electron temperature (figure 4(b)) at the capillary axis for cases of different prepulse current amplitudes together with the case of uniform initial density distribution.…”
Section: Simulation Resultsmentioning
confidence: 91%
“…In the present work, we considered both the preliminary and the main current pulses within a single MHD simulation. The MHD model does not take into account ambipolar diffusion, which for cases of discharge plasma created by current pulses with low amplitude can be a major particle loss mechanism leading to a great deviation from equilibrium [19]. However, it can still be used to obtain and parameterize a nonuniform initial radial density profile that takes place during the prepulse stage in EUV lasers [26] and whose influence on the compression stage of a capillary discharge is to be established.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…We attribute the variation of the plasma column state with the delay time to the radial inhomogeneity of the initial plasma column introduced in Ref. [11]. In Ref.…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. [11], it is found that the initial plasma generated by the pre-pulse is radially inhomogeneous and changes with time. Therefore, when the main pulse flows through the initial plasma at different delay times, the state of the plasma column generated by the main pulse will be different.…”
Section: Resultsmentioning
confidence: 99%